2020
DOI: 10.1038/s41598-020-73368-7
|View full text |Cite
|
Sign up to set email alerts
|

Wide-angle, wide-band, polarization-insensitive metamaterial absorber for thermal energy harvesting

Abstract: We propose a wide-band metamaterial perfect absorber (MPA), using the coupling in the near-field of a quadruple split-ring resonator concentric with crossed ellipses. We designed the MPA with a metal–insulator-metal (MIM) structure for use in thermal energy harvesting. A gradient-based optimization approach was carried out to maximize the absorption of infrared (IR) radiation around 10 μm. Owing to the near-field coupling of resonators with optimal design parameters, the peaks of the absorption responses appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For example, a BMA using multiple discs of various sizes were studied, [344] allowing the formation of broad-band of 2000 nm, with the disadvantage that its absorption was experimentally relatively low, less than 50%. Broadband absorption for thermal energy harvesting was demonstrated by employing a quadruple SRR concentric with the cross-shaped ellipse, [365] which could achieve near-perfect absorption in the IR region. An ultra-broadband and polarization-insensitive MA operated at the MIR region using nine different-sized squarepatch resonators were designed.…”
Section: Planar Design Of Broadband Metamaterials Absorbersmentioning
confidence: 99%
“…For example, a BMA using multiple discs of various sizes were studied, [344] allowing the formation of broad-band of 2000 nm, with the disadvantage that its absorption was experimentally relatively low, less than 50%. Broadband absorption for thermal energy harvesting was demonstrated by employing a quadruple SRR concentric with the cross-shaped ellipse, [365] which could achieve near-perfect absorption in the IR region. An ultra-broadband and polarization-insensitive MA operated at the MIR region using nine different-sized squarepatch resonators were designed.…”
Section: Planar Design Of Broadband Metamaterials Absorbersmentioning
confidence: 99%
“…The emerging field of artificially engineered materials, known as metamaterials, has attracted much attention in the last years for potential use in thermophotovoltaic systems (TPVS) and solar thermal approach [9][10][11][12][13][14]. By demonstrating interesting electromagnetic properties not found in naturally occurring materials, the metamaterial solar absorbers (MSA) have opened a new avenue for solar energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the so-called metamaterial perfect absorber (MPA) was devised by Landy et al [4], which showed a very high absorption but was very thin. The MPAs have high potential for a variety of applications such as for photodetectors [5,6], sensors [7,8], energy harvesters [9,10], and stealth technology [11][12][13]. Since then, the commercial uses of MPAs for healthcare and civilian demands have induced more intensive research on them and their applications.…”
Section: Introductionmentioning
confidence: 99%
“…MPAs can be obtained with a sandwiched multilayer of a periodically-arranged metallic pattern, dielectric-spacer layer, and continuous metallic plate [10,13]. Most of the recent MPAs are hard or stiff, since they are usually fabricated with a hard dielectric layer such as FR4 [4] or silicon [14], which also makes the absorption behavior fixed.…”
Section: Introductionmentioning
confidence: 99%